2021
DOI: 10.3389/fpls.2021.747661
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Molecular Host-Pathogen Interactions During Ramularia Collo-Cygni Infection on Barley

Abstract: Ramularia collo-cygni is the causal agent of Ramularia leaf spot disease (RLS) on barley and became, during the recent decades, an increasing threat for farmers across the world. Here, we analyze morphological, transcriptional, and metabolic responses of two barley cultivars having contrasting tolerance to RLS, when infected by an aggressive or mild R. collo-cygni isolate. We found that fungal biomass in leaves of the two cultivars does not correlate with their tolerance to RLS, and both cultivars displayed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 53 publications
1
12
1
Order By: Relevance
“…The transcriptome dataset has been previously published by us ( Sjokvist et al., 2019 ; Lemcke et al., 2021 ) and was used here for integrative analysis. To link the proteome and transcriptome data, each protein was mapped to the corresponding barley transcript identifier (Ensembl Plants) according to putative paralogue grouping by matching the identifiers from the input source ( Stare et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transcriptome dataset has been previously published by us ( Sjokvist et al., 2019 ; Lemcke et al., 2021 ) and was used here for integrative analysis. To link the proteome and transcriptome data, each protein was mapped to the corresponding barley transcript identifier (Ensembl Plants) according to putative paralogue grouping by matching the identifiers from the input source ( Stare et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown the involvement of ethylene and jasmonic acid signaling, along with the activation of the phenylpropanoid and flavonoid pathways in response to RLS, indicating typical defense processes against necrotrophic pathogens ( Sjokvist et al., 2019 ). The early production of p -coumaroyl-hydroxydehydroagmatin ( p -CHDA) and serotonin, which are both integral components in the process of cell wall fortification, has been identified at the metabolite level ( Lemcke et al., 2021 ). Furthermore, distinct expression levels of kinases, calmodulins, and defense proteins have been described as key differences between the defense responses in sensitive and resistant CVs ( Lemcke et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, novel insights of how plants respond to biological stresses have been uncovered by using a combination of transcriptomics and metabolomics analyses that pinpointed pivotal genes, proteins and metabolites involved in specific plant–pathogen interactions (Kim et al 2021b ; Lemcke et al 2021 ; Li et al 2022 ). Although a growing amount of research utilising a multi-omics approach for studying plant–pathogen interactions has been applied, such studies on oat plant defences, especially inoculated with P. syringae , are scarce.…”
Section: Introductionmentioning
confidence: 99%